Case Report: A Novel Gross Deletion in PAX3 (10.26 kb) Identified in a Chinese Family With Waardenburg Syndrome by Third-Generation Sequencing - Jin, Jie-Yuan; Zeng, Lei; Guo, Bing-Bing; Dong, Yi; Tang, Ju-Yu; Xiang, Rong (Frontiers in Genetics, 2021)
Waardenburg syndrome (WS) is a group of genetic conditions, major inherited in an autosomal dominant pattern, with a global incidence of 1/42000. WS can be divided into at least 4 types, WS1-4, characterized by heterochromia iridis, white forelock, prominent nasal root, dystopia canthorum, hypertrichosis of the medial part of the eyebrows, and deaf-mutism. WS3 is an extremely rare type, with the unique phenotype (abnormality of upper limbs). Heterozygous mutations of PAX3 are commonly associated with WS1, whereas partial or total deletions of PAX3 are often observed in WS3 cases. Deletions together with insertions, translocations, inversions, mobile elements, tandem duplications and complex, constitute structural variants (SVs), which can be fully and accurately tested by third generation sequencing (TGS), a new generation of DNA high-throughput sequencing. In this study, after failing to identify the causative gene by Sanger sequencing, SNP-array and whole-exomes sequencing (WES), we finally detected a heterozygous gross deletion of PAX3 (10.26kb, chr2: 223153899-223164405) in a WS family by TGS. Our description would enrich the genetic map of WS and help us to further understand this disease. This research also demonstrated the value of TGS in clinical genetics researches, once again.